Some characteristics of the adolescence. - María Guillermina Yanes García; Mariela del Carmen Morales (Medisur)
This is a review that focuses the theme of adolescence from their perspective that goes beyond the biological and psychological aspects that appear in the traditional texts . The topic assesses the problem in such a way that the information can be used in the daily practice with the families and with specific groups. The paper analyses the content of classical books as well as articles and publications from different books and updated journals by using inductive-deductive methods as well as literature that has dealt with the topic for years.